Patients' choices and opinions on chorionic villous sampling and non‐invasive alternatives for prenatal testing following preimplantation genetic testing for hereditary disorders: A cross‐sectional questionnaire study. (17th January 2022) - Toft, Christian L. F.; Diemer, Tue; Ingerslev, Hans J.; Pedersen, Inge S.; Adrian, Stine W.; Kesmodel, Ulrik S.
Abstract: Objective: The aim of this study was to investigate choices of and reasoning behind chorionic villous sampling and opinions on non‐invasive prenatal testing among women and men achieving pregnancy following preimplantation genetic testing (PGT) for hereditary disorders. Methods: A questionnaire was electronically submitted to patients who had achieved a clinical pregnancy following PGT at the Center for Preimplantation Genetic Testing, Aalborg University Hospital, Denmark, between 2017 and 2020. Results: Chorionic villous sampling was declined by approximately half of the patients. The primary reason for declining was the perceived risk of miscarriage due to the procedure. Nine out of 10 patients responded that they would have opted for a non‐invasive prenatal test if it had been offered. Some patients were not aware that the nuchal translucency scan offered to all pregnant women in the early second trimester only rarely provides information on the hereditary disorder for which PGT was performed. Conclusion: Improved counseling on the array of prenatal tests and screenings available might be required to assist patients in making better informed decisions regarding prenatal testing. Non‐invasive prenatal testing is welcomed by the patients and will likely increase the number of patients opting for confirmatory prenatal testing following PGT for hereditary disorders. Key points: What is already known about this topic? Invasive prenatal testing is often declined due to the associated risk of miscarriage, and non‐invasive alternatives may increase the number of patients accepting prenatal testing Doctor‐patient communication on prenatal testing has been reported as difficult and patients' knowledge about limitations of prenatal tests have been reported as suboptimal These aspect in the context of preimplantation genetic testing (PGT) for hereditary disorders are not well investigated What does this study add? This study details patients' opinion and choices of invasive and non‐invasive prenatal testing following PGT for hereditary disorders Non‐invasive alternatives may increase the number of patients accepting prenatal testing from 50% to 90%, potentially alleviating concerns during pregnancy and increasing the chance of detecting a misdiagnosis from PGT The study supports previous reports, that communication on the topic is difficult and that patients' knowledge about limitations of prenatal tests is inadequate